2014
DOI: 10.1097/mpg.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Disease Activity Is an Important Factor for Indeterminate Interferon‐γ Release Assay Results in Children With Inflammatory Bowel Disease

Abstract: Although corticosteroid treatment is traditionally considered to be the main risk factor for indeterminate results of IGRA, the disease activity of IBD has even more profound effects on the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
3
14
0
Order By: Relevance
“…A similar association between hypoalbuminemia and indeterminate QFT-GIT test results has been reported previously in hospitalized patients without a diagnosis of IBD. 33 Among patients with IBD, a related observation was made in a study of 72 pediatric IBD patients (59 CD and 14 UC) by Hradsky et al, 34 who reported lower levels of albumin in patients with indeterminate QFT results; however, the association did not remain significant on multivariable analyses. The current study reports an association between low albumin levels and an increased likelihood of indeterminate QFT-GIT results in adult IBD patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A similar association between hypoalbuminemia and indeterminate QFT-GIT test results has been reported previously in hospitalized patients without a diagnosis of IBD. 33 Among patients with IBD, a related observation was made in a study of 72 pediatric IBD patients (59 CD and 14 UC) by Hradsky et al, 34 who reported lower levels of albumin in patients with indeterminate QFT results; however, the association did not remain significant on multivariable analyses. The current study reports an association between low albumin levels and an increased likelihood of indeterminate QFT-GIT results in adult IBD patients.…”
Section: Discussionmentioning
confidence: 92%
“…Because hypoalbuminemia can be the result of malnutrition and inflammation, the latter owing to a greater fractional catabolic rate and increased transfer of albumin in to the extravascular compartment, 35 it is likely that the observed association with hypoalbuminemia reflects the influence of systemic inflammatory burden related to disease activity on QFT-GIT results, as has been reported previously in immune-mediated disorders, including IBD. 34,35 Additional factors such as extremes of age, iron-deficiency anemia, and female sex have been associated previously with indeterminate QFT-GIT results in patients with and without underlying immune-mediated disorders. 36,37 Although patients with indeterminate results in our study had lower hemoglobin levels, this association did not remain significant on multivariable analyses.…”
Section: Discussionmentioning
confidence: 98%
“…However, the optimal strategy in IBD patients has not been yet well-defined as both TST and QFT-G-IT may be negatively affected by disease activity and/or treatment with immunomodulators (IMM), such as azathioprine and methotrexate [6][7][8][9][10][11][12][13][14][15][16][17]. The sensitivity and specificity of TST in the diagnosis of LTB can be limited by high disease activity, malnutrition, treatment with IMM, prior Bacille Calmette-Guerin (BCG) vaccination and/or exposure to environmental mycobacteria [8,9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity and specificity of TST in the diagnosis of LTB can be limited by high disease activity, malnutrition, treatment with IMM, prior Bacille Calmette-Guerin (BCG) vaccination and/or exposure to environmental mycobacteria [8,9,18,19]. On the other hand, the sensitivity of QFT-G-IT may be compromised in patients with highly active disease, especially when they have low albumin levels, and in IMM-treated patients with a low lymphocyte count [68, [10][11][12][13]16,20,21]. Nevertheless, a higher accuracy and cost-effectiveness of IGRA compared to the TST has been reported in IBD patients with a prior BCG vaccination and/or on IMM therapy [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…The rates seem to be lower with advancements in test technique. Rates of indeterminate/invalid results are increased in children who are immunocompromised (especially with HIV infection), who have poorly controlled inflammatory bowel disease, and who have certain co-infections, including hepatitis, malaria, and helminth infection [34][35][36][37]. Indeterminate/invalid IGRA results also occur due to technical error (wrong volume, insufficient mixing, incorrect temperature, prolonged time prior to processing, and laboratory error) [30•, 31•].…”
Section: Igra Limitationsmentioning
confidence: 99%